Studi Struktural Fungsional Dalam Pola Belajar Anak Dari Orang Tua Pekerja Pabrik di Desa Temulus Kecamatan Mejobo - Nakhlah, Riya Ma'alya; Erlita Umi Masytoh; Mutiara Natasya Mu’afida; Nur Fajrie (Universitas Palangka Raya, 2023)
Learning pattern is a process or sequence in learning that can help children understand a topic. Children's learning patterns are different because children have different learning characteristics. This study aims to determine the learning patterns of children of cigarette factory workers in parental guidance based on structural and functional studies. This study uses a case study qualitative research method. Qualitative research is a research technique that provides descriptive information in the form of speech or writing and observed individual behavior. Case studies are an appropriate strategy for research where how or why research questions are used, the researcher has little time to control the events being studied, and the focus of the research is on current phenomena that follow current events. The data collection technique was carried out by means of literature study, recording, interviews, recording and documentation. In this study also used an interactive model with steps that include data collection, presentation and drawing conclusions in analyzing data. Based on the results of the research, it shows that the learning pattern applied by children whose parents work in factories is an independent learning pattern where children study at home independently and are also caged with the help of their older siblings and parents. From this research, there are implications, namely children whose parents are factory workers already have good preparation for learning before starting learning. Making school lesson schedules, taking notes on subject matter. However, noting the subject matter has not been fully implemented properly, because there are children who want to learn when given homework. In addition, there are also children who are able to complete their own homework and are sometimes assisted by their siblings.